(untitled) (Palíndromo, 2021)
A bay that erodes. A time span that expands. It is in the journey to the sensitive of the earth that the intentions and expressions of a changing landscape are explored, in constant transformation: from the variation of the tides, of the full and the empty, to the microerosive scales that are revealed in the tiny dramas of the bodies and languages that also become others. A provocation of the ways of doing science and philosophy through an artistic procedural account; or yet, a tension not only in the way we perceive the world, but in how we make the world today.